Identifying the Determinants of Michinoeki Performance - Takao Ito (Atlantis Press, 2021)
Widely recognized as providing vital services in the transportation sector, it is important to identify the determinants as well as estimate their impact on Michinoeki today. Seemingly, no research has studied their influence using data on all the 1107 Michinoeki established as of April 2017. To attain a better understanding, Japan was divided into nine areas to detect regional differences in the determinants of Michinoeki. The findings of the study indicate that, as expected, there are wide regional variations in the key characteristics of Michinoeki. This paper makes a contribution to the knowledge by: (1) Understanding the status quo of Michinoeki and (2) Identifying important salient factors for their further development. Based on the results, the administrative implications are identified, the research limitations are discussed and avenues for further research are proffered.